Electrochemical Characterization of Bronze Exposed to Outdoor Atmosphere - Otmačić Ćurković, Helena; Mikić, Dajana; Bera, Luka; Kovačević, Ema; Marcelja, Marijana (Chemical and Biochemical Engineering Quarterly, 2021)
The aim of this work was to examine corrosion behaviour of bare and artificial patinated bronzes during exposure to urban outdoor atmosphere. Studies were conducted on copper and two different bronzes in order to evaluate the influence of substrate composition on patina composition and electrochemical behaviour. Additionally, two different patination methods were compared. Corrosion behaviour was examined using electrochemical impedance spectroscopy with gel-electrolyte electrochemical cell. The composition of patina was determined by ATR-FTIR spectroscopy. The obtained results showed that all studied artificial patinas initially decrease the corrosion resistance of copper and bronzes but in time their corrosion resistance improves, and even for certain combinations, artificial patina-bronze corrosion resistance is higher than that of naturally patinated bronze.